The Big Five Personality Traits as a moderator of the Relationship between Foreign Language Classroom Anxiety and Creative Personality - A.K. Erzhanova (Moscow State University of Psychology and Education, 2024)
Foreign language anxiety has received significant attention since many learners experience psychological barriers when learning a language. At the same time, numerous teaching methods aim to create a more efficient approach to language learning. Current research seeks to determine the influence of creative personality and the Big Five Personality Traits (BFPT) on Foreign Language Classroom Anxiety (FLCA). The respondents (N=452) aged between 16 and 45 (M=23,41, SD=7,22) received the Creative Personality Scale by Renzulli, the Ten Item Personality Inventory by Gosling, Rentfrow and Swann, and the Foreign Language Classroom Anxiety Scale by Horwitz evaluating test anxiety, communication apprehension, and fear of negative evaluation. We hypothesize that creative personality predicts FLCA components and the BFPT moderates the relationship between creative personality and FLCA. We found that creative personality significantly predicted FLCA We also found that agreeableness has a moderating effect on the relationship between creative personality and communication apprehension and creative personality and test anxiety, respectively. Based on the findings, we suggested that teachers should pay more attention to the learners’ individual differences. First, it is essential to implement creativity-nurturing methods of teaching more consciously. Second, online or offline teaching methods could decrease communication apprehension depending on the learners’ agreeableness.